Aerosol radiative effects during two desert dust events in August 2012 over the Southwestern Iberian Peninsula - Obregón, Maria (2016)
This study provides an analysis of desert dust aerosol radiative effects in the shortwave solar spectrum. For this purpose, the aerosol radiative forcing (ARF) at the earth's surface was calculated during two desert dust events that occurred during August 2012 over Badajoz (Spain) and Évora (Portugal), both stations are located in southwestern Iberian Peninsula. Aerosol properties from these two AERONET stations have been employed to feed the libRadtran model used to simulate irradiances in the shortwave range at the surface under cloud-free conditions. In addition, simulated irradiances for Évora have been compared with Eppley pyranometer measurements. Simulated irradiance values have been used to calculate ARF values at both sites. The overall mean simulated ARF values for Évora and Badajoz during the first event are − 43.03 and − 43.76 W m− 2, respectively, while, for the second event, the overall mean values are − 19.73 and − 26.07 W m− 2, respectively, indicating that the first event has a greater regional radiative impact than the second one, causing a more pronounced radiate cooling at the surface. The ARF per unit of aerosol optical depth (AOD), called the aerosol radiative forcing efficiency (ARFE), is also evaluated for this shortwave spectral range. The ARFE values obtained for Évora and Badajoz during the first event are − 112.93 ± 6.60 W m− 2 and − 101.63 ± 10.73 W m− 2 per unit of AOD (500 nm), respectively, and, for the second event, − 92.44 ± 9.82 W m− 2 and − 87.85 ± 10.19 W m− 2 per unit of AOD (500 nm), respectively. These values also confirm the previous results, i.e., the first event causes a greater radiate cooling than the second one in both stations, although the second desert dust event is more intense, i.e., with higher aerosol optical depth and PM10 aerosol mass concentration. The presence of absorbing aerosols, together with dust, near the surface during the first event may explain the greater efficiency of this aerosol mixture to reduce the downward shortwave irradiance reaching the surface, inducing a greater radiative cooling than the second event.